Gamma 60Co DL50/30 of Biomphalaria glabrata (Say, 1818) DL50/30 raios gama de 60Co em Biomphalaria glabrata (Say, 1818) - Elaine Barros da Costa CARVALHO; Ana Maria Mendonça de Albuquerque MELO; Mauricy Alves da MOTTA (Revista do Instituto de Medicina Tropical de São Paulo, 1999)
The variation of resistance to 60Co gamma-rays of Biomphalaria glabrata was studied. A population of 480 mollusks was observed during 30 days - distributed in 8 groups of snails isolated and 8 groups of snails in colonies - after exposure (30 snails per group per dose) to increasing doses of gamma radiation. Doses of 10, 20, 40, 60, 80, 160, 320 and 640 Gy from a Gamma-cell 60Co irradiator, were applied to the test groups and two groups control (non-irradiated) of snails - isolated and colony - were kept apart. After have been exposed, the snails were drew back to the aquaria where they were maintained before. The survival was estimated on a daily score of the alive animals in each group-dose, starting after the irradiation exposure day. As a result, the survival self-fertilization forms (DL50/30 = 218.2 Gy) was found greater than in cross-fecundation forms. These data point to a low radio-resistance on the cross-fertilization forms - the sexual reproductive form - which is most found in nature. The lower radio-resistance of the cross-fertilization forms suggests the presence of some sex-linked hormonal factor related to this phenomenon. A variação da resistência entre indivíduos em autofecundação e fecundação cruzada de Biomphalaria glabrata foram estudadas. Uma população de 480 moluscos foi observada durante 29 dias, distribuída em 8 grupos de caramujos isolados e 8 grupos em colônias após a exposição (30 caramujos por grupo-dose) a doses crescentes de radiação gama. Foram usadas doses de 10, 20, 40, 60, 80, 160, 320 e 640 Gy de um irradiador Gamma-Cell 60Co. Dois grupos não irradiados - isolado e colônia - foram separados como controle e após a irradiação todos os caramujos voltaram para aquários onde viviam antes. A sobrevida foi estimada pela contagem diária dos animais vivos em cada grupo-dose, a partir do dia da irradiação. O resultado mostrou maior sobrevivência nos grupos isolados (DL50/30 = 218.2 Gy) que nos grupos colonizados (DL50/30 = 59 Gy). Estes dados apontam para uma baixa radio-resistência nos grupos colonizados - com forma de reprodução sexuada - que são mais comuns na natureza. A baixa resistência observada sugere a presença de fatores humorais e hormônios sexuais ligados ao fenômeno